School vouchers and student achievement: Recent evidence, remaining questions - Cecilia Elena Rouse; Lisa Barrow (Federal Reserve Bank of Chicago, 2008)
In this article, we review the empirical evidence on the impact of education vouchers on student achievement, and briefly discuss the evidence from other forms of school choice. The best research to date finds relatively small achievement gains for students offered education vouchers, most of which are not statistically different from zero. Further, what little evidence exists regarding the potential for public schools to respond to increased competitive pressure generated by vouchers suggests that one should remain wary that large improvements would result from a more comprehensive voucher system. The evidence from other forms of school choice is also consistent with this conclusion. Many questions remain unanswered, however, including whether vouchers have longer-run impacts on outcomes such as graduation rates, college enrollment, or even future wages, and whether vouchers might nevertheless provide a costneutral alternative to our current system of public education provision at the elementary and secondary school level.
Keywords: 330; Schulfinanzierung; Voucher; Bildungsverhalten; USA